2021
DOI: 10.3390/ma14112705
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Nanocomposites Based on Oxidized Carbon Nanohorns as Sensing Layers for Room Temperature Resistive Humidity Sensing

Abstract: This paper presents the relative humidity (RH) sensing response of a resistive sensor employing sensing layers based on a ternary nanocomposite comprising graphene oxide-oxidized carbon nanohorns-polyvinylpyrrolidone (GO-CNHox–PVP), at 1/1/1, 1/2/1, and 1/3/1 w/w/w mass ratios. The sensing structure is composed of a silicon substrate, a SiO2 layer, and interdigitated transducers (IDT) electrodes, on which the sensing layer is deposited via the drop-casting method. The morphology and the composition of the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…For instance, Figure 7b shows Raman spectra recorded in four different positions of the CNHox/TiO 2 /PVP = 2/1/1 (w/w/w) film plotted in red, grey, green, and blue colors. It can be observed that three active Raman bands (D, G, and 2D) were recorded at the wavenumbers of 1318.3, 1591.9, and 2627.8 cm −1 , which confirms the presence of the nanocarbonic material (CNHox) [27,30,34]. One can also identify specific anatase TiO 2 bands as follows: E g1 mode at 149.1 cm −1 (very sharp and intense in all the samples, except for 1/1/1), B 1g at 397.6 cm −1 , A 1g at 513.9 cm −1 , and E g3 at 634.7 cm −1 [47][48][49].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…For instance, Figure 7b shows Raman spectra recorded in four different positions of the CNHox/TiO 2 /PVP = 2/1/1 (w/w/w) film plotted in red, grey, green, and blue colors. It can be observed that three active Raman bands (D, G, and 2D) were recorded at the wavenumbers of 1318.3, 1591.9, and 2627.8 cm −1 , which confirms the presence of the nanocarbonic material (CNHox) [27,30,34]. One can also identify specific anatase TiO 2 bands as follows: E g1 mode at 149.1 cm −1 (very sharp and intense in all the samples, except for 1/1/1), B 1g at 397.6 cm −1 , A 1g at 513.9 cm −1 , and E g3 at 634.7 cm −1 [47][48][49].…”
Section: Resultsmentioning
confidence: 69%
“…Holey carbon nanohorns (CNHox), a type of carbon nanohorns with increased hydrophilicity, have proven to be promising alternatives as a sensitive coating within the design of the RH chemoresistors [27]. Moreover, binary nanocomposites such as CNHox/PEG-PPG-PEG (poly (ethylene glycol)-poly block (propylene glycol)-poly block (ethylene glycol), CNHox/PVP (polyvinylpyrrolidone), and ternary nanocomposites from the type CNHox/GO (graphene oxide)/PVP were successfully explored as sensing layers for RH monitoring [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34]. Among these types of materials, one can mention, inter alia, graphene oxide [35][36][37], carbon nanotubes [38][39][40], amorphous carbon [41], nanodiamond [42,43], nanocones [44], fullerenes and their derivatives [45,46], carbon nanocoils [47], holey carbon nanohorns (CNHox) and their nanocomposites [48][49][50][51][52][53][54][55], hydrogenated amorphous carbon [56], oxidized carbon nanoonions [57][58][59][60], carbon quantum dots [61].…”
Section: Methodsmentioning
confidence: 99%
“…H + or H 3 O + ions produced by the dissociation of adsorbed water on the surface are the conduction mechanism in metal-oxide-based humidity sensors. Recent works [ 226 , 227 ] studied and described the adsorption of water on metal oxide surfaces and the mechanism of sensing water vapor. As a result of water adsorption on metal oxide surfaces, humidity decreased the sensitivity of metal oxide sensors ( Figure 15 ) [ 228 , 229 ].…”
Section: Gas-sensing Applicationsmentioning
confidence: 99%